Effects of environmental stresses on physiochemical stability of β-carotene in zein-carboxymethyl chitosan-tea polyphenols ternary delivery system. (1st May 2020) - Ba, Chujie; Fu, Yuying; Niu, Fuge; Wang, Mei; Jin, Bing; Li, Zeya; Chen, Guowen; Zhang, Hao; Li, Xiaomeng
Highlights: Ternary complex nanoparticles were fabricated with zein, CMCS and TP. Tea polyphenols enhanced color maintainance of β-carotene in aqueous phase. β-carotene embedded ternary systems showed high physiochemical stability. Abstract: β-Carotene is a natural nutrient that serves as a natural food colorant. However, the weak physical stability restricts its development in food industrial production. Here, the influences of a variety of external environmental conditions on the stability of β-carotene enriched zein-carboxymethyl chitosan (CMCS)-tea polyphenols (TP) ternary composite nanoparticles were investigated. Compared with zein unitary and zein-CMCS binary complexes, it was interesting to note that ternary complexes had the best stability against color fading and there was little impact on its nanoparticle size during storage with change in temperature. Besides excellent antioxidant properties, ternary complexes were extremely effective in inhibiting β-carotene color degradation when exposed to ultraviolet light. Based on our results, the novel zein-CMCS-TP nanoparticles are expected to be an effective delivery system to encapsulate hydrophobic bioactive compounds, which is a promising approach to improve their storage stability against external environmental stresses.